미국 푸드스탬프제도의 운영실태와 시사점 - 최지현 (KREI, 2003)
The purpose of the U.S. Food Stamp Program is to end hunger and improve nutrition and health. It helps low-income households who buy the food they need for a nutritionally adequate diet. Korea could introduce food assistance program such as U.S. food Stamp Program, mainly being focused on improving nutrition and health for low income families. In order to launch this program successfully, the operation system should be related to current cash assistance system for low income families, and the infrastructure for EBT(Electronic Benefit Transfer) system should be constructed in food market.
Keywords: 푸드스탬프; 전자지불제도; 저소득층 식품비지원; 영양개선; Food Stamp; Electronic Benefit Transfer; EBT; Food Assistance for low-income households; Improvement of Nutrition